Using umbilical cord blood as a source of paediatric packed red blood cells: Processing and quality control - Risso, Mariane Aparecida; Deffune, Elenice [UNESP]; Luzo, Ângela Cristina Malheiros (Wiley, 2023)
Background and Objectives: Umbilical cord blood (UCB) has been used as a source of red blood cells (RBCs) for neonatal/paediatric transfusion purposes. This study adopted two different procedures to obtain umbilical RBC (U-RBC) to compare its quality control parameters to those of fractionated adult RBC (A-RBC), for paediatric purposes. Materials and Methods: UCB units (24) were filtered and processed based on two different methods, namely, conventional/manual (P1;n12) and automatic (P2;n12). They were compared to five fractionated A-RBCs. U-RBC and A-RBC were stored for 14 days and had their haematological, biochemical, haemolytic and microbiological parameters analysed at D1, D7 and D14. Cytokines and growth factors (GFs) in residual U-RBC plasma were measured. Results: Mean volume of processed U-RBC units was 45 mL for P1 and 39 mL for P2; the mean haematocrit level reached 57% for P1 and 59% for P2. A-RBC recorded a mean volume of 44 mL. Haematologic and biochemical parameters analysed in U-RBC and A-RBC presented similar behaviours during storage time, except for parameter values, which differed between them. Pro-inflammatory and immunomodulatory cytokines, as well as GFs, were higher in U-RBC residual plasma than in that A-RBC. Conclusion: UCB can be processed into RBC based on either manual or automated protocols. U-RBC units met the referenced quality parameters defined for A-RBC. Some features, mainly the biochemical ones, should be further investigated to help improve quality parameters, with emphasis on differences found in, and particularities of, this material and on recipients of this new transfusion practice.
Keywords: control quality; growth factors; paediatric transfusion; red blood cell; umbilical cord blood